PENERAPAN PARK AND RIDE DI STASIUN BEKASI - Mega Suryandari; Achmad Wisakcono; Imma widyawati Agustin (Diponegoro University, 2015)
The purpose of this research is to know the implementation of park and ride at BekasiStation. The method of analysis in this research is the assessment of parking performance based onstandards and parking user perception with Kano-model, and the Analytic-Hierarchy-Process(AHP) to analyze the implementation of park and ride at Bekasi Station. The results show thatparking performance doesn’t meet the standard. The problem of parking performance at BekasiStation are view from two perspectives, namely: the peak accumulation which is more than itscapacity and parking index which is more than 1 (one). Improved performance based on userperception parking with Kano Model, the main priority is obvious parking lines and the parkingstandard. The priority of implemention of park and ride at Bekasi Station is provideparking28.48%. From the results of this research, the writter recommends to build a parking in conformitywith the parking user’s perception for short term solution and the implementation of park and ridefor the long term solution.